2013
DOI: 10.1002/ejlt.201300021
|View full text |Cite
|
Sign up to set email alerts
|

Discarded species in the west Mediterranean sea as sources of omega‐3 PUFA

Abstract: Five discarded fish species in the Alboran Sea, namely axillary seabream (Pagellus acarne), small‐spotted catshark (Scyliorhinus canicula), sardine (Sardina pilchardus), horse mackerel (Trachurus mediterraneus), and bogue (Boops boops) were evaluated as novel sources for the production of omega‐3 polyunsaturated fatty acids (PUFAs). The lipid content of the five species varied significantly within the different seasons, being maximum in spring for axillary seabream, small‐spotted catshark, and bogue (5.1, 2.7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 32 publications
(41 reference statements)
4
15
0
Order By: Relevance
“…However, García‐Moreno et al . () reported that sardine oil obtained by the same extraction process also presented cholesterol (7.5%w) and phospholipids (0.8%w). Although these compounds could be also contained in the extracted oils obtained in this work, they were not identified probably due to the different polarity of the mobile phase employed to develop the silica plates.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…However, García‐Moreno et al . () reported that sardine oil obtained by the same extraction process also presented cholesterol (7.5%w) and phospholipids (0.8%w). Although these compounds could be also contained in the extracted oils obtained in this work, they were not identified probably due to the different polarity of the mobile phase employed to develop the silica plates.…”
Section: Resultsmentioning
confidence: 86%
“…These results are in agreement with our previous work that reported similar protein and ash content for sardine in all the seasons, 17%w and 3%w, respectively. However, the lipid content considerably varied within seasons, reaching minimum values in March (0.6%w) and maximum in June (13.6%w) (García‐Moreno et al ., ). Thus, from these measurements, it was revealed that July, when sardine presented a lipid amount up to 17.7%w, is even a better month to obtain a higher yield of oil from this species.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, commercial species such as sardine (Sardina pilchardus), horse mackerel (Trachurus mediterraneus) and axillary seabream (Pagellus acarne) are also discarded in this fishery due to quota restrictions, minimal landing-size requirements or high-grading practices. These species present valuable protein contents, which are practically constant during the year ranging from 17 to 23% depending on the species (García-Moreno, Pérez-Gálvez, Morales-Medina, Guadix, & Guadix, 2013). Therefore, added-value products such as bioactive peptides produced by enzymatic proteolysis can be obtained from the protein fraction of these discarded fish species.…”
Section: Introductionmentioning
confidence: 99%